Log in to add a comment

Log in to add a comment

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

Given,

(4x + 5x)(4x - 5y) - (3x + 2y)(3x - 2y)

first , see the first term ( i mean 4x)

multiply it with (4x - 5y)

u will get,

16x² - 20xy

like wise multiply +5x with (4x - 5y)

u will get,

20 x²- 25 xy

now (4x + 5x)(4x-5y) = 16x²-20xy+20x²-25xy

----------------------------------------------------------------------------

now,u have

-(3x +2y)(3x-2y)

similarly how u did above ,

multiply -3x with ( 3x-2y)

u will get,

-9x²+6xy

now,

u should take -2y and mul with (3x-2y)

u will get,

-6xy + 4y²

now-(3x+2y)(3x-2y) = -9x²+6xy-6xy+4y²

----------------------------------------------------------------

now, totally,

(4x+5x) (4x-5y)-(3x2y)(3x-2y)=16x²-20xy+20x²-25xy-9x²+6xy-6xy+4y²

arrange in an easy way to solve,

= 16x²+20x²-9x²+4y²-20xy-25xy+6xy-6xy

= 37x²+4y²-45xy

here, +6xy and - 6xy gets cancelled

**u need to concentrate on symbols **:

(i) plus×plus = plus

(ii)plus ×minus = minus

(iii) minus × minus = plus

(iv) minus ×plus = minus

(4x + 5x)(4x - 5y) - (3x + 2y)(3x - 2y)

first , see the first term ( i mean 4x)

multiply it with (4x - 5y)

u will get,

16x² - 20xy

like wise multiply +5x with (4x - 5y)

u will get,

20 x²- 25 xy

now (4x + 5x)(4x-5y) = 16x²-20xy+20x²-25xy

----------------------------------------------------------------------------

now,u have

-(3x +2y)(3x-2y)

similarly how u did above ,

multiply -3x with ( 3x-2y)

u will get,

-9x²+6xy

now,

u should take -2y and mul with (3x-2y)

u will get,

-6xy + 4y²

now-(3x+2y)(3x-2y) = -9x²+6xy-6xy+4y²

----------------------------------------------------------------

now, totally,

(4x+5x) (4x-5y)-(3x2y)(3x-2y)=16x²-20xy+20x²-25xy-9x²+6xy-6xy+4y²

arrange in an easy way to solve,

= 16x²+20x²-9x²+4y²-20xy-25xy+6xy-6xy

= 37x²+4y²-45xy

here, +6xy and - 6xy gets cancelled

(i) plus×plus = plus

(ii)plus ×minus = minus

(iii) minus × minus = plus

(iv) minus ×plus = minus